If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 8n + -6q = 0 Solving 4m + 8n + -6q = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8n' to each side of the equation. 4m + 8n + -8n + -6q = 0 + -8n Combine like terms: 8n + -8n = 0 4m + 0 + -6q = 0 + -8n 4m + -6q = 0 + -8n Remove the zero: 4m + -6q = -8n Add '6q' to each side of the equation. 4m + -6q + 6q = -8n + 6q Combine like terms: -6q + 6q = 0 4m + 0 = -8n + 6q 4m = -8n + 6q Divide each side by '4'. m = -2n + 1.5q Simplifying m = -2n + 1.5q
| 18=7-(a+10) | | 13x^2-24x-288=0 | | 8m^2+44m+60=0 | | 9(2h+7)+3w= | | k/3=1.5 | | 1/3(8-x)=8-x/2 | | 288=72(h) | | 1/2lnx=-1 | | (2t+7)+6=73 | | 6.28*3/2*13/6x | | 1/2(3j) | | 0.210=3735x-0.006588 | | -(1/3)^1 | | 9t^2-48t+39=0 | | 10n+14=74 | | 3x^2+4x-mn=0 | | .35x=36 | | 5v^2+44v-9=0 | | 3x^2+4x-m*n=0 | | 5v+44v-9=0 | | Ln(x)+ln(x+7)=5 | | Ln(x)-ln(x+7)=5 | | 9h-12h=54-13 | | x+(x)(2)+x-3=39 | | 3w^2+11w+6=0 | | P=0.5q+0.5 | | 4=×/14 | | 3g^2-14g+16=0 | | -54=6k | | 5-10x-6x+6= | | 6x^2+30x+12=0 | | 6x^2+30x+1=0 |